Implementasi Corporate Social Responsibility PT. Amman Mineral Nusa Tenggara Dalam Membentuk Citra Perusahaan - Khailifa, Quincy Diena; Khusnia, Hartin Nur; Yohanes, Yulanda Trisula Sidarta; Miharja, Dian Lestari (Tuturlogi: Journal of Southeast Asian Communication, 2023)
The rapid growth of CSR implementation in Indonesia is directily proportional to the growth of the public concerns and demands. However, there are still many kinds of problems and failures that are found due to the lack of the corporate's understandings regarding the CSR itself, even though the success of a CSR plays a big role in forming a corporate's image. In West Nusa Tenggara, one of the corporates that actively implement their CSR programs is PT. Amman Mineral Nusa Tenggara. Thus, the objective for this research was to know and understand the implementation of CSR done by PT. Amman Mineral Nusa Tenggara through economic empowerment in forming a company image. The results of this research show that the implementation of CSR by PT. Amman Mineral Nusa Tenggara through economic empowerment is done through collaborations with implementing partner to form a community within the beneficiaries and to carry out face-to-face training and assistance. This implementation indicates that PT. Amman Mineral Nusa Tenggara has implemented the main principles that determine the success of CSR itself, which are sustainability, accountability, and transparency. Keywords: